Association of Uric Acid With Blood Pressure in Hypertension Between Treatment Group and Non-treatment Group - Ding, Ning; Long, Yong; Li, Changluo; He, Liudang; Su, Yingjie (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aimed to explore the association between uric acid (UA) and blood pressure (BP) in hypertension treatment and non-treatment groups. Methods: A cross-sectional study with 6,985 individuals from the National Health and Nutrition Examination Survey (NHANES) was performed. Multiple linear regression analysis was performed to explore the relationship of UA and BP in hypertension between the treatment group (n = 5,983) and the non-treatment group (n = 1,002). Results: A significantly negative association was discovered in SBP (β, −0.36 [95% CI, −0.71, −0.01]) and DBP (β, −0.47 [95% CI, −0.69, −0.26]) in the hypertension treatment group. In the hypertension non-treatment group, the associations between UA and BP including SBP, DBP were both an inverted U-shape. The inflection point of SBP and DBP was 7 and 7.5 mg/dl, respectively. For SBP, the association was positively significant (β, 3.11 [95% CI, 1.67, 4.56]) before the inflection point of 7 mg/dl. However, after the inflection point of 7 mg/dl, the association was negative (β, −5.44 [95% CI, −8.6, −2.28]). For DBP, the inflection point was 7.5 mg/dl, and the effect size was positive (β, 1.19 [95% CI, 0.37, 2.01]) before the inflection point. However, after it, the effect size was negative (β, −3.24 [95% CI, −5.72, −0.76]). Conclusion: The association between UA and BP was negative in the hypertension treatment group. In the hypertension non-treatment group, the associations between UA and BP including SBP and DBP were both an inverted U-shape.